Recent developments in carbon‐based electrodes surface modification for zinc bromine flow battery - Yanhong Li; Xiaoyun Sun; Lin Meng; Xingxing Wang; Boxue Ouyang; Deren Wang; Chenyu Zhao; Haochen Hu (IET Energy Systems Integration)
Abstract Zinc‐bromine flow batteries (ZBFBs) hold promise as energy storage systems for facilitating the efficient utilisation of renewable energy due to their low cost, high energy density, safety features, and long cycle life. However, challenges such as uneven zinc deposition leading to zinc dendrite formation on the negative electrode and parasitic hydrogen evolution reaction during charging pose risks of membrane puncturing and short circuits, thereby limiting energy density improvements. Additionally, the sluggish and non‐reversible Br2/Br− redox reaction hampers battery power density enhancements. Given that electrode properties significantly influence the rate and reversibility of these redox reactions, modifications to the negative and positive electrodes are crucial. While inert carbon‐based electrodes are favoured for their corrosion resistance and conductivity, their hydrophobic nature and low electrochemical activity restrain the performance of ZBFBs. The authors present a comprehensive review of recent advancements in both negative and positive electrode modifications in ZBFBs. It also puts forward future research directions aimed at overcoming existing challenges, with the ultimate objective of promoting the efficient utilisation of ZBFBs.